KOMPETENSI PEDAGOGI GURU DALAM PEMANFAATAN TEKNOLOGI UNTUK PEMBELAJARAN - Putra, Lovandri Dwanda; Zakiya, Faza; Salsabila, Annisa; Salsabila, Sovia (JS (JURNAL SEKOLAH), 2023)
Abstract: The purpose of this study is to find out and analyze how the pedagogical competence of SD Negeri Siluk teachers in utilizing technology for learning. This research was conducted by descriptive qualitative method. The technique used to collect data is interviews. The subject of the study was a grade II teacher. Based on the results of the study, it is known that Siluk State Elementary School already has technology facilities for learning and teachers have received training to use the technology as a form of teacher pedadogy competency development. The conclusion of this research is that SD Negeri Siluk has learning technology and the teachers are competent in the use of technology for learning. Keyword: Teacher pedagogy competence, Primary School, educational technology Abstrak: Tujuan penelitian ini adalah untuk mengetahui dan menganalisis bagaimana kompetensi pedagogi guru SD Negeri Siluk dalam pemanfaatan teknologi untuk pembelajaran. Penelitian ini dilakukan dengan metode kualitatif deskriptif. Teknik yang digunakan untuk mengumpulkan data adalah wawancara. Subjek penelitian adalah guru kelas II. Berdasarkan pada hasil penelitian diketahui bahwa SD Negeri Siluk sudah memiliki fasilitas teknologi untuk pembelajaran dan para guru telah mendapat pelatihan untuk menggunakan teknologi tersebut sebagai bentuk pengembangan kompetensi pedadogi guru. Kesimpulan penelitian ini yaitu SD Negeri Siluk memiliki teknologi pembelajaran dan para guru telah berkompetensi dalam pemanfaatan teknologi untuk pembelajaran.Kata Kunci: Kompetensi pedagogi guru, Sekolah Dasar, teknologi pendidikan